Effectiveness of Momentum and Contrarian Strategies: A Systematic Literature Review Across Countries, Models, and Market Conditions - Wayan Eka Heltyani; Sudirman, I Made Surya Negara (PT. Global World Scientific, 2025)
This study synthesizes empirical findings related to the effectiveness of momentum and contrarian investment strategies in various global stock markets during the period 1993-2023. Using a Systematic Literature Review (SLR) approach of 25 peer-reviewed scientific articles, this study analyzes the strategy characteristics, success determinants, and market context that affect the profitability of both approaches. The results show that momentum strategies are superior in the short term, especially in markets with low to medium information efficiency, while contrarian strategies are more effective in the long term, especially in markets with overreaction tendencies and retail investor dominance. The effectiveness of both strategies is highly contextual, depending on market microstructure, macroeconomic conditions, the risk model used, as well as the characteristics of market participants. Recent research trends point to the importance of adaptive strategies, such as volatility-based momentum, switching strategies, as well as the integration of behavioral factors such as investor attention. The study also identifies research gaps in cross-market validation, transaction costs, and response to geopolitical dynamics. The findings provide practical implications for investors and policymakers to develop more resilient and adaptive investment strategies.